Identification of Groundwater Potential Zones Utilizing GIS, RS and AHP: A Case Study of Rupandehi District in Nepal - Thapa, Lawaj; K.C., Niraj (LTU Journal of Advanced Computing & Engineering, 2026)
Groundwater is a vital natural resource currently under immense pressure due to overexploitation and a lack of systematic planning. This study aims to identify and map groundwater potential zones (GWPZ) in the Rupandehi district of Nepal using an integration of Geographic Information System (GIS), Remote Sensing (RS), and the Analytic Hierarchy Process (AHP). Seven thematic layers—rainfall, geology, slope, land use/land cover (LULC), soil, drainage density, and lineament density—were integrated within a GIS platform. Multi-Criteria Decision Analysis (MCDA) via AHP was employed to weigh these layers based on their relative importance. The resulting GWPZ map categorizes the district into High, Moderate, and Low potential zones. Findings indicate that 34% of the area possesses high potential, 45% moderate, and 21% low potential. High-potential zones are primarily in the southern Terai plains, while northern mountainous regions exhibit lower potential. This study provides a data-driven guide for water resource managers to ensure sustainable groundwater.